Characterization of a Polymer‐Based, Fully Organic Prosthesis for Implantation into the Subretinal Space of the Rat. Issue 17 (30th May 2016) - Antognazza, Maria Rosa; Di Paolo, Mattia; Ghezzi, Diego; Mete, Maurizio; Di Marco, Stefano; Maya‐Vetencourt, José Fernando; Maccarone, Rita; Desii, Andrea; Di Fonzo, Fabio; Bramini, Mattia; Russo, Angela; Laudato, Lucia; et al.
Abstract : Replacement strategies arise as promising approaches in case of inherited retinal dystrophies leading to blindness. A fully organic retinal prosthesis made of conjugated polymers layered onto a silk fibroin substrate is engineered. First, the biophysical and surface properties are characterized; then, the long‐term biocompatibility is assessed after implantation of the organic device in the subretinal space of 3‐months‐old rats for a period of five months. The results indicate a good stability of the subretinal implants over time, with preservation of the physical properties of the polymeric layer and a tight contact with the outer retina. Immunoinflammatory markers detect only a modest tissue reaction to the surgical insult and the foreign body that peaks shortly after surgery and progressively decreases with time to normal levels at five months after implantation. Importantly, the integrity of the polymeric layer in direct contact with the retinal tissue is preserved after five months of implantation. The recovery of the foreign‐body tissue reaction is also associated with a normal b‐wave in the electroretinographic response. The results demonstrate that the device implanted in nondystrophic eyes is well tolerated, highly biocompatible, and suitable as retinal prosthesis in case of photoreceptor degeneration. Abstract : A three‐layer fully organic retinal prosthesis made of conjugated polymers layered onto a silk fibroin scaffold is engineered. The pseudo‐color rendering of the ultrastructure shows the two polymeric layers, made of PEDOT:PSS (blue) and P3HT (red) spin‐coated onto silk fibroin (yellow). The device implanted in nondystrophic eyes is well tolerated, highly biocompatible, and suitable as retinal prosthesis in case of photoreceptor degeneration.